People and Data: solving planetary challenges together - Vanalli, Chiara; Howerton, Emily; Yang, Fuhan; Tran, Thu Nguyen-Anh; Hu, Weiming (Frontiers in Environmental Science, 2024)
The advancement of computing and information collection technologies has created vast amounts of data describing the world surrounding us. Yet, our planet continues to face unprecedented challenges, including climate change and biodiversity loss. How do we effectively use this information in an open and collaborative way to tackle these planetary-scale issues? We propose a stronger synergistic integration between people and data as we work toward a healthy planet: crowd empowerment in the collection and analysis of data as well as in the identification and implementation of actionable solutions. We use our unique experience as a diverse winning team of the EY Better Working World 2022 global data challenge to illustrate the great potential and current limitations of such an approach. With the objective of fighting biodiversity loss, we were asked to develop a predictive frog multi-species distribution model using occurrence data, gathered from the FrogID app, and environmental conditions. Despite the great potential of global data challenges focused on planetary health, they comprise about 6% of all challenges in the last five years. Moreover, though open in principle, in practice, pre-existing disparities limit the inclusion of a diverse crowd. To address existing gaps, we propose practical guidelines to realize the ‘People & Data’ vision: fostering collaboration, seeking funding, enhancing diversity, and ensuring long-term sustainability. In this way, we can tackle the great challenges our world is facing.